The Influence of Education Level and Length of Service on Employee Per-formance in Ogan Komering Ulu Regency - Muhayunina; Yunita sari; Rini Efrianti (Institute for Law and Economics Studies, 2026)
This study aims to analyze the influence of education level and work tenure on the performance of Civil Servants (ASN) at the Secretariat of the DPRD of Ogan Komering Ulu Regency. The research method uses a quantitative approach with a saturated sample of all 64 ASN employees. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that education level and work tenure, both partially and simultaneously, have a positive and significant effect on employee performance. The independent variables explain 33.1% of the performance variation (R²=0.331), while the remaining 66.9% is influenced by other factors. The study concludes by emphasizing the importance of HR policies that integrate the improvement of educational qualifications with knowledge management from work experience.